Procedural Gaps in Libya’s National Anti-Corruption : عناصر الضُّعف الإدارية في الهيئة الوطنية لمكافحة الفساد في ليبيا - Suliman Elguddafi Kahoul, Aisha; Daud, Mohd Zaidi; Jamaludin, Mohd Hafiz (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2022)
This study aimed to highlight the most significant procedural gaps in the law and work of the Body through its institutional structure, the powers and authorities conferred with providing solutions to address those gaps. The study concluded that, at this time, the Body is not fulfilling its duty to combat manifestations of corruption and delinquency because the State’s lack of force in law and order. Moreover, the academic specialization of the Body’s staff does not qualify them for functional competence in the performance of their functions unless they have the ability and mastery of research, investigation and inference skills in corruption offences. Furthermore, the Body’s role was limited only to an inference power that often limited its performance in anti-corruption; it was supposed to be given preliminary investigative power to fulfil its desired and required role. Also, non-issuance of the executive Body’s regulation, made it paralyzed from its functions which should have done so in order to be able to separate and determine the procedures governing its establishment law and how it would be implemented. In addition to the absence of safeguards protecting Body’s members from all forms of intimidation or threat while it was supposed to enact a law allowing them to exercise their duties and functions without fear or concern. Consequently, procedural gaps in the law and work of the Body require legal details of the working mechanisms of the Body’s staff.